The Utilization of Instagram Broadcast Channels as a Digital Marketing Communication Media in Building Consumer Loyalty - Zakiah, Kiki; Ihsan Permana Sumpena, Muhammad; Yuanita, Yenni (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2025)
Social media has become the primary space of digital marketing communication that allows brands to build more targeted relationships with consumers. One of the innovations developed by Instagram is the Broadcast Channel, which is a one-way communication channel that provides access to exclusive information to audiences who consciously choose to join. However, academic studies on the role of one-way digital communication in building consumer loyalty are still relatively limited. This study aims to analyze the use of Instagram Broadcast Channel as a digital marketing communication medium in building consumer loyalty in the Alln Knitwear online shop. This research uses a qualitative method with a case study approach through in-depth interviews, observations, and documentation. The results of the study show that Broadcast Channels are used to convey product information directly, involve consumers in product selection through a co-creation mechanism, and provide special offers that strengthen consumers' sense of belonging, trust, and emotional closeness to the brand. The novelty of this study lies in the finding that one-way digital marketing communication voluntarily chosen by consumers can serve as a relational mechanism in building loyalty. Theoretically, this study emphasizes the position of one-way communication as an alternative to shaping consumer loyalty in the study of digital marketing communication, which has so far emphasized dialogical communication. Practically, the findings of this study provide a reference for business people in optimizing social media features efficiently to retain consumers in the digital marketing era.